Antarctic Phanerozoic landscape evolution along the Transantarctic basin from thermochronology - Timothy Paulsen; Jeffrey Benowitz; Stuart Thomson; John Encarnación; Anne Grunow; Paul Layer; Maddie Young (Earth and Planetary Science Letters, 2025)

Disease outbreak data to inform decision-making: the role of disease spread models in the Lao P.D.R. African Swine Fever epidemic, 2019 - Nina Matsumoto; Tariq Halasa; Kathrin Schemann; Syseng Khounsy; Bounlom Douangngeun; Watthana Thepagna; Phouvong Phommachanh; Jarunee Siengsanan-Lamont; James Young; Jenny-Ann Toribio; Russell Bush; Stuart D. Blacksell; et al. (Tropical Animal Health and Production, 2025)
Understanding the spread of African Swine Fever (ASF) between villages in the southeast-Asian, low − middle income country context is critical if this high impact disease is to be controlled by good policy and effective field activities in these resource-poor settings. Using governmental reporting data from the 2019 outbreak of ASF in Lao People’s Democratic Republic, spatial clustering techniques were used to identify clusters of outbreak villages. Then Approximate Bayesian Computation with Sequential Monte Carlo was used to estimate the transmission parameters of ASF virus between the villages within these clusters. We used a simple disease spread model to understand the impact of parameter estimation on predicted disease spread and thus decision-making. Six clusters of radius 16 to 153km were identified over the 7 month outbreak period. Within these clusters, the basic reproduction number (R 0 ) ranged from 13 to 32 between-villages and whole-village infectious periods ranged from 62 to 68 days. The final model outputs were compared to the original field report data. We found that the ability of the estimated parameters to match field data was heavily reliant on how the original field surveillance data was reported. Specifically, in situations in which cases in a cluster appeared to have been reported as batches (lack of temporal specificity) our modelling approach failed to produce satisfactory outputs in terms of model fit and precision of estimates. This study demonstrates that surveillance for transboundary diseases not only has immediate benefit for disease response, but that good quality surveillance data is valuable for informing future planning for disease response via appropriately parameterised disease spread models. There is a need for ongoing quality control of surveillance and support for field veterinary services to ensure quality data that can be used to drive policy and decision-making.

Accelerating and standardising IUCN Red List assessments with sRedList - Victor Cazalis; Moreno Di Marco; Alexander Zizka; Stuart H.M. Butchart; Manuela González-Suárez; Monika Böhm; Steven P. Bachman; Michael Hoffmann; Ilaria Rosati; Francesco De Leo; Martin Jung; Ana Benítez-López; et al. (Biological Conservation, 2024)

Novel estimation of African swine fever transmission parameters within smallholder villages in Lao P.D.R - Nina Matsumoto; Michael P. Ward; Tariq Halasa; Kathrin Schemann; Syseng Khounsy; Bounlom Douangngeun; Watthana Thepagna; Phouvong Phommachanh; Jarunee Siengsanan-Lamont; James R. Young; Jenny-Ann L. M. L. Toribio; Russell D. Bush; et al. (Tropical Animal Health and Production, 2024)
African Swine Fever (ASF) disease transmission parameters are crucial for making response and control decisions when faced with an outbreak, yet they are poorly quantified for smallholder and village contexts within Southeast Asia. Whilst disease-specific factors − such as latent and infectious periods − should remain reasonably consistent, host, environmental and management factors are likely to affect the rate of disease spread. These differences are investigated using Approximate Bayesian Computation with Sequential Monte-Carlo methods to provide disease parameter estimates in four naïve pig populations in villages of Lao People’s Democratic Republic. The villages represent smallholder pig farmers of the Northern province of Oudomxay and the Southern province of Savannakhet, and the model utilised field mortality data to validate the transmission parameter estimates over the course of multiple model generations. The basic reproductive number between-pigs was estimated to range from 3.08 to 7.80, whilst the latent and infectious periods were consistent with those published in the literature for similar genotypes in the region (4.72 to 6.19 days and 2.63 to 5.50 days, respectively). These findings demonstrate that smallholder village pigs interact similarly to commercial pigs, however the spread of disease may occur slightly slower than in commercial study groups. Furthermore, the findings demonstrated that despite diversity across the study groups, the disease behaved in a consistent manner. This data can be used in disease control programs or for future modelling of ASF in smallholder contexts.

Prioritizing the reassessment of data‐deficient species on the IUCN Red List - Victor Cazalis; Luca Santini; Pablo M. Lucas; Manuela González‐Suárez; Michael Hoffmann; Ana Benítez‐López; Michela Pacifici; Aafke M. Schipper; Monika Böhm; Alexander Zizka; Viola Clausnitzer; Carsten Meyer; et al. (Conservation Biology, 2023)
Despite being central to the implementation of conservation policies, the usefulness of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species is hampered by the 14% of species classified as data‐deficient (DD) because information to evaluate these species’ extinction risk was lacking when they were last assessed or because assessors did not appropriately account for uncertainty. Robust methods are needed to identify which DD species are more likely to be reclassified in one of the data‐sufficient IUCN Red List categories. We devised a reproducible method to help red‐list assessors prioritize reassessment of DD species and tested it with 6887 DD species of mammals, reptiles, amphibians, fishes, and Odonata (dragonflies and damselflies). For each DD species in these groups, we calculated its probability of being classified in a data‐sufficient category if reassessed today from covariates measuring available knowledge (e.g., number of occurrence records or published articles available), knowledge proxies (e.g., remoteness of the range), and species characteristics (e.g., nocturnality); calculated change in such probability since last assessment from the increase in available knowledge (e.g., new occurrence records); and determined whether the species might qualify as threatened based on recent rate of habitat loss determined from global land‐cover maps. We identified 1907 species with a probability of being reassessed in a data‐sufficient category of >0.5; 624 species for which this probability increased by >0.25 since last assessment; and 77 species that could be reassessed as near threatened or threatened based on habitat loss. Combining these 3 elements, our results provided a list of species likely to be data‐sufficient such that the comprehensiveness and representativeness of the IUCN Red List can be improved.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Climate predicts both visible and near‐infrared reflectance in butterflies - Changku Kang; Sehyeok Im; Won Young Lee; Yunji Choi; Devi Stuart‐Fox; Blanca Huertas (Ecology Letters, 2021)
Climatic gradients frequently predict large‐scale ecogeographical patterns in animal coloration, but the underlying causes are often difficult to disentangle. We examined ecogeographical patterns of reflectance among 343 European butterfly species and isolated the role of selection for thermal benefits by comparing animal‐visible and near‐infrared (NIR) wavebands. NIR light accounts for ~50% of solar energy but cannot be seen by animals so functions primarily in thermal control. We found that reflectance of both dorsal and ventral surfaces shows thermally adaptive correlations with climatic factors including temperature and precipitation. This adaptive variation was more prominent in NIR than animal‐visible wavebands and for body regions (thorax‐abdomen and basal wings) that are most important for thermoregulation. Thermal environments also predicted the reflectance difference between dorsal and ventral surfaces, which may be due to modulation between requirements for heating and cooling. These results highlight the importance of climatic gradients in shaping the reflectance properties of butterflies at a continent‐wide scale.

Lessons Learned from Running a Conference in the Time of COVID-19 and the Silver Linings of Shifting to Online - Hannah Power; Madelaine Broadfoot; Annette Burke; Paul Donaldson; Rosanne Hart; Kendall Mollison; David Schmidt; Stuart Young (Oceanography, 2020)

A framework for evaluating the impact of the IUCN Red List of threatened species - Jessica Betts; Richard P. Young; Craig Hilton‐Taylor; Michael Hoffmann; Jon Paul Rodríguez; Simon N. Stuart; E.J. Milner‐Gulland (Conservation Biology, 2020)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species, a species extinction risk assessment tool, has been guiding conservation efforts for over 5 decades. It is widely assumed to have been instrumental in preventing species from moving closer to extinction and driving recoveries. However, the impact of the IUCN Red List in guiding conservation has not been evaluated. We conducted, transcribed, and coded interviews with experts who use the IUCN Red List across a range of sectors to understand how the list is used in conservation. We developed a theory of change to illustrate how and why change is expected to occur along causal pathways contributing to the long‐term goal of the IUCN Red List and an evaluation framework with indicators for measuring the impact of the IUCN Red List in generating scientific knowledge, raising awareness among stakeholders, designating priority conservation sites, allocating funding and resources, influencing development of legislation and policy, and guiding targeted conservation action (key themes). Red‐list assessments were the primary input leading to outputs (scientific knowledge, raised awareness), outcomes (better informed priority setting, access to funding and resource availability, improved legislation and policy), and impact (implemented conservation action leading to positive change) that have resulted in achievement of IUCN Red List goals. To explore feasibility of attributing the difference made by the IUCN Red List across themes, we studied increased scientific knowledge, raised awareness, access to funding and resource allocation, and increased conservation activity. The feasibility exploration showed increased scientific knowledge over time identified through positive trends in publications referring to the IUCN Red List in the literature; raised awareness of the list following high IUCN activity identified by peaks in online search activity; an increased proportion of conservation funding bodies requesting IUCN Red List status in the application process; and, based on interviews with Amphibian Specialist Group members, red‐list assessments were essential in connecting relevant stakeholders and ensuring conservation action. Although we identified the IUCN Red List as a vital tool in global conservation efforts, it was challenging to measure specific impacts because of its ubiquitous nature. We are the first to identify the influence of the IUCN Red List on conservation.

Predicting the spatial distribution of allele frequencies for a gene associated with tolerance to eutrophication and high temperature in the reef-building coral, Acropora millepora, on the Great Barrier Reef - Young K. Jin; Stuart Kininmonth; Petra B. Lundgren; Madeleine J. H. van Oppen; Bette L. Willis (Coral Reefs, 2020)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Trpc6 inactivation confers protection in a model of severe nephrosis in rats - Eun Young Kim; Parisa Yazdizadeh Shotorbani; Stuart E. Dryer (Journal of Molecular Medicine, 2018)

How can wages sustain a living? By getting ahead of the curve - Stuart Colin Carr; Molefe Maleka; Ines Meyer; Marie-Louise Barry; Jarrod Haar; Jane Parker; James Arrowsmith; Christian Yao; Darrin Hodgetts; Harvey Jones; Amanda Young-Hausner; Emeline Afeaki-Mafile’o; et al. (Sustainability Science, 2018)

Hemodynamics in Idealized Stented Coronary Arteries: Important Stent Design Considerations - Susann Beier; John Ormiston; Mark Webster; John Cater; Stuart Norris; Pau Medrano-Gracia; Alistair Young; Brett Cowan (Annals of Biomedical Engineering, 2016)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Similar increases in muscle size and strength in young men after training with maximal shortening or lengthening contractions when matched for total work - Daniel R. Moore; Mark Young; Stuart M. Phillips (European Journal of Applied Physiology, 2012)

Biomarkers of Fruit and Vegetable Intake in Human Intervention Studies: A Systematic Review - Francina R. Baldrick; Jayne V. Woodside; J. Stuart Elborn; Ian S. Young; Michelle C. McKinley (Critical Reviews in Food Science and Nutrition, 2011)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Inducible expression of TGFβ, Snail and Zeb1 recapitulates EMT in vitro and in vivo in a NSCLC model - Gretchen M. Argast; Joseph S. Krueger; Stuart Thomson; Isabela Sujka-Kwok; Krista Carey; Stacia Silva; Matthew O’Connor; Peter Mercado; Iain J. Mulford; G. David Young; Regina Sennello; Robert Wild; et al. (Clinical & Experimental Metastasis, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

BRCA1/2 mutation analysis in male breast cancer families from North West England - D. G. R. Evans; Mike Bulman; Karen Young; Emma Howard; Stuart Bayliss; Andrew Wallace; Fiona Lalloo (Familial Cancer, 2008)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Atypical size selection of captive school prawns, Metapenaeus macleayi , by three recreational fishing gears in south‐eastern Australia - Matt K. Broadhurst; Russell B. Millar; Damian J. Young; Michael E. L. Wooden; Stuart Rowland (New Zealand Journal of Marine and Freshwater Research, 2004)
Three manipulative experiments were done to estimate the selectivity of conventional and new sizes and configurations of mesh for school prawns, Metapenaeus macleayi , in three south‐eastern Australian recreational fishing gears (haul, push, and scoop nets). The treatment meshes examined were: (1) conventional‐sized, diamond‐shaped mesh used in all gears (20 mm in scoop nets and 30 mm in push and haul nets); (2) 30 mm in scoop nets; and (3) 40‐mm diamond‐ and (4) 23‐mm square‐shaped mesh in all gears. In all experiments, known quantities of school prawns (6–24 mm carapace length (CL)) were placed in purpose‐built enclosures, monitored to ensure no experimental‐induced stress (as measured by changes in L‐lactate in their haemolymph) and the replicate treatments of the various gear configurations deployed. Escapees from the various treatment nets were collected from the enclosures using fine‐meshed nets. Logistic selection curves were derived for all treatment nets and specific comparisons made within and among gears. All nets had 50% retention lengths (L 50 ) comparable to other penaeid‐catching gears with similar mesh sizes, but most had selection ranges (SRs) that were atypically inflated. The large SRs were attributed to a combination of factors that included the mesh geometry and towing speed of the gears and the behaviour of school prawns. The 20‐mm scoop net had the smallest selection parameters, retaining >99% of individuals larger than 13 mm CL. Mesh size in this gear would need to be increased to at least 30 mm to allow some maturing prawns (>18 mm CL) to escape.

Corticosteroid-serotonin interactions in depression: a review of the human evidence - Richard J. Porter; Peter Gallagher; Stuart Watson; Allan H. Young (Psychopharmacology, 2004)

Effect of sub-chronic hydrocortisone on responses to amphetamine in normal male volunteers - Stuart Watson; Allan H. Young; Andrea J. Hearn; Margaret S. Smith; Bruce M. Owen; Peter Gallagher (Psychopharmacology, 2004)

Elevated prolactin responses to l-tryptophan infusion in medication-free depressed patients - Richard J. Porter; Peter Gallagher; Stuart Watson; Margaret S. Smith; Allan H. Young (Psychopharmacology, 2003)

Dispersion Moments of Fumigating Plumes – Lidar Estimates and Pdf Model Simulations - Ashok K. Luhar; Stuart A. Young (Boundary-Layer Meteorology, 2002)

The effects of sub-chronic administration of hydrocortisone on hormonal and psychological responses to L-tryptophan in normal male volunteers - Richard J. Porter; Peter Gallagher; Stuart Watson; Brian S. Lunn; Allan H. Young (Psychopharmacology, 2002)

Response to A. Henderson-Sellers and K. McGuffie - Simon Shackley; Peter Young; Stuart Parkinson (Climatic Change, 1999)

Uncertainty, Complexity and Concepts of Good Science in Climate Change Modelling: Are GCMs the Best Tools? - Simon Shackley; Peter Young; Stuart Parkinson; Brian Wynne (Climatic Change, 1998)

Sun injury to cut potato seed - W. C. Edmundson; C. F. Clark; C. H. Metzger; J. C. Miller; Wm Stuart; L. C. Young (American Journal of Potato Research, 1939)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)